Model-Based RL Decision-Making for UAVs Operating in GNSS-Denied, Degraded Visibility Conditions with Limited Sensor Capabilities - Sebastien Boiteau; Fernando Vanegas; Julian Galvez-Serna; Felipe Gonzalez (Drones, 2025)
Autonomy in Unmanned Aerial Vehicle (UAV) navigation has enabled applications in diverse fields such as mining, precision agriculture, and planetary exploration. However, challenging applications in complex environments complicate the interaction between the agent and its surroundings. Conditions such as the absence of a Global Navigation Satellite System (GNSS), low visibility, and cluttered environments significantly increase uncertainty levels and cause partial observability. These challenges grow when compact, low-cost, entry-level sensors are employed. This study proposes a model-based reinforcement learning (RL) approach to enable UAVs to navigate and make decisions autonomously in environments where the GNSS is unavailable and visibility is limited. Designed for search and rescue operations, the system enables UAVs to navigate cluttered indoor environments, detect targets, and avoid obstacles under low-visibility conditions. The architecture integrates onboard sensors, including a thermal camera to detect a collapsed person (target), a 2D LiDAR and an IMU for localization. The decision-making module employs the ABT solver for real-time policy computation. The framework presented in this work relies on low-cost, entry-level sensors, making it suitable for lightweight UAV platforms. Experimental results demonstrate high success rates in target detection and robust performance in obstacle avoidance and navigation despite uncertainties in pose estimation and detection. The framework was first assessed in simulation, compared with a baseline algorithm, and then through real-life testing across several scenarios. The proposed system represents a step forward in UAV autonomy for critical applications, with potential extensions to unknown and fully stochastic environments.